From Delocalization to Performances of Japaneseness: Shifting Identities in Transnational Popular Music in and after Japan's Period of "Gross National Cool". (3rd February 2015) - Tonelli, Chris
Abstract : This paper examines several trends in Japanese and Japan-related popular music that coincide with the rise and decline of "Gross National Cool, " Japan's recent period of heightened foreign consumption of Japanese cultural products. Using two case studies, the music of Utada Hikaru and of Puffy, I argue this period saw Japanese artists shift from attempts to "internationalize" their music to strategies of marked performance of Japaneseness. A third case study examines the role performances of Japaneseness played in the work of the popular American artist Gwen Stefani during this period. Her image at this time involved being constantly flanked by an entourage of her "Harajuku Girls, " four women whose visible Asianness served for years to articulate Stefani to the image of Cool Japan. Together, these three case studies explore some of the ways performances of Japaneseness became a strategy for success in transnational popular music between 2000 and 2010.